Medico-Legal Conclusions Caused by Misevaluation of the Schmorl’s Node, which is Rarely Seen in Children (Case Report) - Aşırdizer, Mahmut (The Bulletin of Legal Medicine, 2021)
Schmorl’s node is disruption of the cartilaginous endplate and herniation of the nucleus pulposus into the vertebral body in the period after losing of nuclear material through the cartilage plate. This article is about a 12-year-old boy, who was injured in a traffic accident, traumatic vertebral compression fracture was defined and was established a causality between this lesion and the traffic accident. As a result of consultation with neurosurgery and pediatric radiology, it was concluded that this lesion was SN and was not associated with the traffic accident. Because of the case presented in this article, the literature was reviewed, the concept and procedure of causality in forensic medicine applications was discussed and the importance of multidisciplinary approach was emphasized in such cases.